RETRACTED: Mobile-assisted means of developing ecologic awareness in contects of modern legislation - Toshmatov Oybek; Rasulova Mahbuba (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001